Mapping the scientific research in the income of farmers, 2021: a bibliometric review - Anti Anti; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2021)
This study aims to analyze the factors that are thought to affect the income of farmers in the village of Toraja Regency. The variables used are factors that are thought to influence and determine the size of the net income that will be received by farmers, namely, the area of ​​rice fields, the amount of fertilizer use, the use of liquid pesticides, the use of labor in one growing season. The analytical method used is quantitative analysis method using multiple linear regression model and bibliometrics analysis. The data used are primary data obtained from the research location through observation and interviews and supporting data obtained from the village government, the Indonesian Central Statistics Agency (BPS), the media and others. The results of this study show that the variables, namely the amount of fertilizer, liquid pesticides, and the use of labor in paddy fields significantly affect the income of rice farmers in Toraja district.